2015
DOI: 10.1080/19338244.2015.1129301
|View full text |Cite
|
Sign up to set email alerts
|

Urinary heavy metals in Hispanics 40–85 years old in Doña Ana County, New Mexico

Abstract: As, Cd, Pb, and U exposure among older Hispanic adults residing in underserved communities in southern New Mexico was investigated. Personal information was obtained by standardized interview from 188 adults age 40–85y. Urinary metal concentrations were measured and compared to results from the National Health and Nutritional Examination Survey (NHANES). Urinary As and U in study participants significantly (P<0.05) exceeded NHANES reference values. Elevated urinary As concentration was significantly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Thirty full-text articles were reviewed for further assessment. Five articles were excluded because they were duplicate publications [ 14 , 15 , 22 , 24 , 28 ]; another five were excluded because Cd content was measured [ 33 37 ], three studies were excluded because the outcome was gestational diabetes mellitus [ 17 , 18 , 25 ], three were reviews [ 38 40 ], two were excluded because outcomes were related to chronic kidney disease [ 41 ] or renal glomerular damage [ 42 ] and one was excluded because the exposure was Cd in the toenail [ 13 ]. Finally, eleven studies met meta-analysis criteria and were included (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty full-text articles were reviewed for further assessment. Five articles were excluded because they were duplicate publications [ 14 , 15 , 22 , 24 , 28 ]; another five were excluded because Cd content was measured [ 33 37 ], three studies were excluded because the outcome was gestational diabetes mellitus [ 17 , 18 , 25 ], three were reviews [ 38 40 ], two were excluded because outcomes were related to chronic kidney disease [ 41 ] or renal glomerular damage [ 42 ] and one was excluded because the exposure was Cd in the toenail [ 13 ]. Finally, eleven studies met meta-analysis criteria and were included (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…iAs is a naturally occurring element in the earth's crust and both humans and wildlife are exposed to iAs through food and water. Estimates of over 100-million people worldwide are exposed to levels exceeding World Health Organization (WHO)-established limits ( Adams et al, 2016 ; Farzan et al, 2016 ; Yang et al, 2009 ). The first prospective cohort study of people chronically exposed to arsenic has revealed an increase in all-cause and chronic disease mortalities ( Ahsan et al, 2006 ; Argos et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends have been previously reported in the Maternal-Infant Research on Environmental Chemicals (MIREC) pregnancy cohort of Canadian women, such that statistically significant associations between women’s age and increased urinary and blood As were observed. 52 , 65 Age-related increases in urinary As and iAs have been observed in other adult populations in the U.S., including in a population of older low-income Hispanic adults in New Mexico 66 and a population of older adults residing in Nevada. 67 …”
Section: Discussionmentioning
confidence: 84%